PENGARUH PERILAKU RESIKO, KEPEMILIKAN INSTITUSI DAN KINERJA TERHADAP KEBANGKRUTAN BANK UMUM DI INDONESIA - Swandari, Fifi (Journal of Indonesian Economy and Business, 2002)
This paper investigates the impact of risk taking behavior, institution ownership and performance on bank failure. I predict that risk-taking behavior has positive impact on bank failure, institution ownership and performance have negative impact on bank failure. Result shows that risk taking behavior and institution ownership give little support to hypothesis. Performance has result as predicted. The result suggests that the impact of risk taking behavior and institution ownership needs further investigation.Keyword: risk taking, institutional ownership, performance, bank failure